Fermented Grain Beverage Supplementation Following Exercise Promotes Glycogen Supercompensation in Rodent Skeletal Muscle and Liver - Tsubasa Shibaguchi; Rie Ishizawa; Atsushi Tsuji; Yuya Yamazaki; Keizo Matsui; Kazumi Masuda (Universitas Pendidikan Indonesia, 2017)
The purpose of this study was to investigate the effects of post-endurance exercise fermented grain beverage (FGB) supplementation on glycogen reaccumulation in rat skeletal muscle and liver. Twelve-hour fasted male Wistar rats, 10-week-old, performed five 30-min bouts of swimming separated by 5-min rest periods in order to deplete tissue glycogen storage. The rats were orally administrated either water, glucose, or FGB in 30, 60, 90, and 120 min after the exercise. Immediately and/or 240 min after the exercise, soleus and gastrocnemius muscles and liver were removed and analyzed. A large glycogen reaccumulation was observed in skeletal muscles and liver at 240 min after the exercise when either glucose or FGB were ingested. This response tended to be greater in FGB-treated than in glucose-treated animals, particularly in liver and gastrocnemius muscle. These results suggest that post-endurance exercise FGB supplementation enhances glycogen restoration in both skeletal muscle and liver.